Szymon Wiesenthal — na tropie nazistów i sprawiedliwości - Stankowski, Witold (Wydawnictwo Uniwersytetu Wrocławskiego, 2009)
2008 was a year of the hundredth anniversary of Simon Wiesenthal’s birth. He is remembered by history as “The Nazi-hunter” “Nazijager” in German. This man persistently searched for justice in the matter of reckoning up with totalitarianism especially Hitlerite one. As events taking place after World War II showed, it was not easy, and in some cases outright impossible, to judge a war crime and to put perpetrator before court. These problems plagued Simon Wiesenthal. He strove to calm himself and believe that a perpetrator of a crime will sooner or later stand trial for his deeds. His motto was: “Murderers shall never live in peace.” Simon Wiesenthal lost his almost whole family during World War II. 89 members of his family died – they were murdered in ghettos and camps. Simon and his wife Cyla survived. These tragic occurrences influenced Simon Wiesenthal’s life philosophy. He made it his vocation to pursue Hitlerite criminals. No professional apparatus was at his disposal. He established the Center of Documentation in Linz later transferring it to Vienna. He believed that thanks to human and institutional help it would be possible to apprehend and try war criminals. This faith in the existence of justice became his life philosophy. In order to achieve his aims, he gave his person, activeness, industriousness and intransigence. He felt that by constantly reminding about the existing problems concerning the apprehension and punishment of Hitlerite criminals he would not let the world forget about tragedies and injuries sustained by millions of people. Justice, however defective it might be, cannot be ignored – Wiesenthal claimed. His life philosophy of hunting down Nazi criminals and bringing them before the justice system derived from the question formed by Wiesenthal himself: why did he endure, why did he survive Holocaust? Does this fact put an obligation on him to try to remove the veils covering this crime? Wiesenthal put the problem of justice in its mythical context. Did he do anything so important that he deserved a pass to life? He did not think so. That is why his philosophy was based on the feeling of guilt. He did not deserve miraculous escape; therefore, he had to erase his guilt by relentlessly pursuing Nazi criminals in order to even the accounts and compensate for his undeserved survival. During his life “The Nazi-hunter” was wondering what would happen to his archival heritage and gathered documentation after his death. After talks with representatives of Austrian government, national societies and international associations, the idea was born to create the institution called Wiener Wiesenthal Institut fur Holocaust-Studien Vienna Wiesenthal Institute for Holocaust Studies.
Keywords: Wiesenthal, Szymon (1908-2005); nazizm; sprawiedliwość